The Philosophy of Rationalist - Saroh, Septiani (Yayasan Sembilan Pemuda Indonesia, 2024)
Rationalism or the rationalist movement is a philosophical school which states that truth can be obtained only through proof, logic and analysis of facts. All sources of knowledge and rationalism come from the mind or are realistically rational. This article provides information regarding the fields of economic philosophy, politics, education and religion. According to Hastuti (2018), Rational Theology believes that knowledge about God and good and bad can be obtained with the power of reason. Therefore, thanking God before the revelation is mandatory. Apart from that, because reason can also know good and bad, everyone is obliged to do good things such as being honest, acting fairly and abandoning bad things such as lying and being blindly unjust. Meanwhile, in traditional theology, the human mind has no ability except knowing God. Meanwhile, the other three things can only be known through revealed information. Therefore, the issue of the good or bad value of an action cannot be determined by reason but must be determined by revelation. Lying, for example, is a bad act because revelation states it so.